An exploratory research of morphological patterns of Aedes albopictus (Diptera: Culicidae) in Misiones, Argentina - Siches, Julieta A. (2022)
Aedes albopictus (Diptera: Culicidae) is a vector of several arboviruses, distributed from Misiones to the northern of Corrientes province in Argentina. Its wide distribution around the world has been attributed to rapid reproduction and adaptive capacity to different environments. The objective of this work was to search morphological patterns of Aedes albopictus populations, using wing geometric morphometric analysis. Our study area was the city of Puerto Iguazu and Iguazu National Park, characterized in three environments: urban (UR), periurban (PU) and sylvatic (SY).